High-order thinking skill in contextual teaching and learning of mathematics based on lesson study for learning community - ., Hobri; Septiawati, Ice; Cahya Prihandoko, Antonius (International Journal of Engineering and Technology, 2018)
This research aimed to develop Mathematics instructional instruments by using Contextual Teaching and Learning (CTL) Based on Lesson Study for Learning Community (LSLC) on â€œSequence and Seriesâ€ Learning Material for the tenth grade students of vocational school as well as to know its effect on the studentsâ€™ high-order thinking skill. The method used is mixed methods with concurrent triangulation strategy model namely research and development method with Thiagarajan model combined with quantitative method using non equivalent control group design quasi experimental pretest-posttest. The research subjects were the students of SMKN 1 Panji of Situbondo regency, from which two classes were chosen as research sample, class X Accounting 2 as the control class and class X Accounting 3 as the ex-perimental class. High-order thinking skill is measured by using essay test. Assumption test of normality and homogeneity of variance was tested before analyzing the data. The result of the first test showed that the data were not normally distributed. Therefore, the data were ana-lyzed by using Mann-Whitney analysis. The research results showed that: (1) the instructional instruments resulted is valid, the implementa-tion of the instructional instruments is in practical and effective; (2) the significance value (2-tailed) is 0.000 (p < 0.05), which indicated that the application of learning by using CTL Based on LSLC had a significant effect on the studentsâ€™ high-order thinking skill.Â Â